Komiks jako profanowanie mitu - Szyłak, Jerzy (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
Traditionally, literary works are considered to be displaced myths. Comic book researchers would like to treat the objects of their analysis in the same way. Comics, however, are counted as mass culture, and are therefore treated differently. A work of art can open a human being to the transcendent. On the other hand, a comic imposes a kind of distance on the reader and is rather a story about how someone experiences the sacred, a voice in the discussion about the nature of religious experiences. Comics’ specificity, on the other hand, is conducive to creating stories which are mocking and critical of other types of messages. This does not mean, however, that there are no comic artists who try to offer the reader the possibility of contact with the transcendent.